Low-frequency vibrational modes of stable glasses - Lijin Wang (Nature Portfolio, 2019)
The nature of the vibrational modes of amorphous solids is of fundamental interest, but assessing them is challenging due to very long equilibrium times involved. Wang et al. numerically model the localized low-frequency vibrational modes in glasses and show the sensitivity of their populations to glass stability.